Failure of diffusion weighted MRI to detect severe hypoxic-ischemic encephalopathy in a child - Rajapakse, Thilinie; Ramaswamy, Vijay; Scozzafava, James; Sinclair, D. Barry (Journal of Pediatric Neurology, 2010)
Diffusion weighted imaging is currently the standard of care in the early imaging of hypoxic-ischemic brain injury. Its use has been well described in adults; however, there is a paucity of data regarding its use and reliability in the immature brain. Here we report a case of a 17-month-old who died from a diffuse hypoxic ischemic injury secondary to asphyxiation where there was a failure of diffusion-weighted imaging to show diffuse injury. The electroencephalogram, neurological examination and computerized tomography all suggested global hypoxic-ischemic injury, yet the diffusion weighted imaging showed only focal ischemia at 48 hours post injury. We discuss possible mechanisms underlying the failure of diffusion-weighted imaging to provide an accurate measure of the severity of this child's injury, and highlight the importance of the neurological examination in determination of prognosis in hypoxic-ischemic brain injury.
Keywords: Hypoxic-ischemic brain injury; diffusion weighted imaging; ischemia; neurological outcome